2019
DOI: 10.1002/aur.2227
|View full text |Cite
|
Sign up to set email alerts
|

Burden of major depressive disorder and quality of life among mothers of children with autism spectrum disorder in urban bangladesh

Abstract: This cross‐sectional study examined the burden of depression and quality of life (QoL) among mothers of children with autism spectrum disorder (ASD) attending six schools offering special educational services for children with ASD in urban Dhaka, Bangladesh. All consenting mothers were 18 years of age and older and met criteria for major depressive disorder (MDD) on the Structured Interview for DSM‐V‐TR Research Version‐non patient edition administered by trained raters. QoL was assessed by the EuroQol five‐di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 65 publications
(77 reference statements)
2
10
0
1
Order By: Relevance
“…When analyzing the primary caregivers of children with autism, the statistical results showed that the primary caregiver of 135 children with autism out of 171 respondents was the mother, accounting for 78.9% of the total. It's consistent with the previous studies (Samadi et al, 2014;Naheed et al, 2020;Hu et al, 2020). It is evident that mothers are still the primary caregivers of children with autism.…”
Section: Mother As the Primary Caregiver For Children With Autismsupporting
confidence: 93%
“…When analyzing the primary caregivers of children with autism, the statistical results showed that the primary caregiver of 135 children with autism out of 171 respondents was the mother, accounting for 78.9% of the total. It's consistent with the previous studies (Samadi et al, 2014;Naheed et al, 2020;Hu et al, 2020). It is evident that mothers are still the primary caregivers of children with autism.…”
Section: Mother As the Primary Caregiver For Children With Autismsupporting
confidence: 93%
“…In this study, the WeChat-based parenting training that was targeted at mothers with children with autism had statistically significant impacts on anxiety and depression levels, which is consistent with previous studies' findings [20,33]. Several studies reported that anxiety and depression levels among mothers with children with autism were higher than among mothers with neurotypical children [34][35][36]. During the COVID-19 pandemic, the public felt anxiety, depression, despair, and many other emotional reactions [37].…”
Section: Effects Of the Wechat-based Parenting Trainingsupporting
confidence: 89%
“…The two selected schools would have at least 100-150 children with ASD registered in a given year. On the basis of the previous study findings, we anticipate that about 26% mothers would be diagnosed as having MDE, and we would find a total of 52 to 78 mother-child pairs from two schools for study recruitment [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, Naheed and colleagues at the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b) estimated that 45% of the mothers of ASD children and adolescents aged 3-17 years, who were enrolled in a special school for ASD, had suffered an episode of major depressive disorder (MDD), half of whom reported a current major depressive episode (MDE) [ 15 , 16 ]. Remarkably, most mothers (70%) had a college degree or a higher level of education [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation